Persepsi Khalayak Warga Kampung Kota Surabaya tentang Radio Kampung sebagai Media Informasi Kependudukan - Anak Agung Istri Satvikadewi; Merry Fridha Tri Palupi; Diana Yemima; Hesti Rochmat Wulandani (LPPM Stikosa - AWS, 2021)
This study aims to describe the perception of the people of Surabaya about ‘radio kampung’. Basically, Radio Kampung is a community-based radio that was initiated, organized, and give its most benefits to the kampung inhabitant. The Surabaya’s Department of Population and Civil Registration (Dispendukcapil) wish radio kampung to become a strategic partner in disseminating information about civil administration services, considering the importance of involving the community at a smaller population level in the information dissemination process. The Community Satisfaction Index (IKM) Report showed that service quality of the The Surabaya’s Department of Population and Civil Registration (Dispendukcapil) showed a decrease in the in 2020 by 3 points compared to the achievement in 2019, although it was still categorized as good. To improve their service quality, Dispendukcapil started with increasing public information access to information about civil administration procedures, one of which is by initiating multi-platform information media, including radio. The survey results show that ‘radio kampung’ is perceived as a radio organized by, from and for the villagers (47%). 51.1% audience expect the ‘radio kampung’ to be an online radio that can be accessed by anyone via computers and gadgets.